A high-fat diet protects C57BL/6 mice from Plasmodium berghei ANKA infection in an experimental malaria study - Soares, Sara Malaguti Andrade; Gualberto, Ana Cristina Moura; da Costa, Augusto Cesar; Gonçalves, Diego Assis; Gameiro, Jacy (Frontiers in Tropical Diseases, 2023)
Introduction It is well known that dietary changes have a significant impact on the immune system, and modifications in lipid balance may contribute to disease progression in several cases. Malaria is still a major global health concern, and the development of the disease has already been linked to the host’s nutritional status, so it’s critical to understand how environmental factors, such as dietary variations, can influence the outcome of infection. We therefore investigated the effect of a short-term diet in a murine model of experimental cerebral malaria. Methods For this, male C57BL/6 mice were fed a high fat diet containing 60% of the calories from lipids for 5 days. Following this period, the animals were infected with Plasmodium berghei ANKA, and parasitemia, survival, and neurological scores were compared. Considering that one of the first elimination routes of the intracellular parasite is oxidative stress, the antioxidant N-acetylcysteine was administered to assess whether the protection would be reversed. Results and discussion Animals fed a hyperlipidic diet reacted the same way to infection even after NAC administration. Unlike the control group, which died after eight days of infection with roughly 7% parasitized red blood cells, the hyperlipidic diet group was resistant to infection, with no clinical signs and no increase in blood parasitemia. Several proinflammatory cytokines such as TNF-α IFN-γ and IL-6 were increased in the spleen of both infected groups, regardless of their diet. The provision of a high-fat diet to mice for as little as 5 days completely prevents Plasmodium berghei ANKA infection in C57BL/6 mice, while the treatment of an antioxidant failed to reverse the parasite protection.